BOE Meeting with Reutlingen University and Promotion activities for Business Engineering program in Sabah - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
FIM conducted a Meeting with Reutlingen University (24 - 28 Feb, 2016) in Promenade Hotel, Kota Kinabalu, Sabah. During this meeting various issues were discussed and the main focus was on Business Engineering Program.